2006
DOI: 10.1186/1471-2407-6-142
|View full text |Cite
|
Sign up to set email alerts
|

The relation between deoxycytidine kinase activity and the radiosensitising effect of gemcitabine in eight different human tumour cell lines

Abstract: Background: Gemcitabine (dFdC) is an active antitumour agent with radiosensitising properties, shown both in preclinical and clinical studies. In the present study, the relation between deoxycytidine kinase (dCK) activity and the radiosensitising effect of gemcitabine was investigated in eight different human tumour cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…However, response rates are low and rarely exceed 20% (27,28). Reported DCK enzymatic activity in tumors ranges from 5 to 18 pmol/h per mg of protein, and previous studies have found these values to correlate with sensitivity to dFdC (15,29). The DCK activity in L1210 wt leukemia cells was 0.4 nmol/h per mg, well within the range observed in other tumors.…”
Section: Stratification Of Dck-positive and -Negative Tumors By Usingsupporting
confidence: 66%
“…However, response rates are low and rarely exceed 20% (27,28). Reported DCK enzymatic activity in tumors ranges from 5 to 18 pmol/h per mg of protein, and previous studies have found these values to correlate with sensitivity to dFdC (15,29). The DCK activity in L1210 wt leukemia cells was 0.4 nmol/h per mg, well within the range observed in other tumors.…”
Section: Stratification Of Dck-positive and -Negative Tumors By Usingsupporting
confidence: 66%
“…Radiation elevates dCK mRNA and protein levels [ 38 ], and there is a clear correlation between dCK levels and radiosensitizing effects of gemcitabine [ 39 ]. dCK adds the first phosphoryl group to DAC and is the rate-limiting enzyme of the overall process of converting DAC to its triphosphate form that incorporates into DNA [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also in concordance with other data in the literature which state that gemcitabine radiosensitization is more pronounced in cells with high basal dCK activity. 42 We should note, that Pauwels et al 43 recently reported that dCK activity weakly correlated to gemcitabine radiosensitization. Besides the high basal dCK level, another possible explanation for the radiosensitizing effect of gemcitabine is that irradiation itself can induce dCK activity in Gl261 cells by twofold (G Sa´fra´ny and S De´saknai, personal communication, 2005), which, in turn might further improve gemcitabine metabolism and amplify its toxic effect.…”
Section: -31mentioning
confidence: 90%